Relationship between corporate social responsibility and performance: The moderating effect of financial leverage - Wafa Sahraoui; Rimvie Enoc Kaboré (Institute of Computer Science (IOCS), 2023)
As an extension of theoretical work from several socio-political approaches, such as stakeholder theory and agency theory, the purpose of this study is to examine the nonlinear effects of corporate social responsibility (CSR) on firms’financial performance and identify the degree of financial leverage as a channel through which CSR exerts its influence on firm financial performance. The present research was carried out in France, where the legislation on sustainable development reports is significant. Using a sample of 70 French firms listed on the SBF 120 index, a factorial interaction model is estimated for the period 2005-2014. We find that the relationship between CSR and firms’ financial performance is non linear, exhibiting an inverted U-shaped pattern. In particular, our results reveal that the CSR financial performance relationship is moderated by firms-specific factors, namely financial leverage. Our study demonstrates also the important of the evolution in the dynamic behavior of CSR effect on the financial performance firms.